2015
DOI: 10.1175/jhm-d-13-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Heat Fluxes above a Suburban Reservoir: A Case Study from Germany

Abstract: With the objective of quantifying turbulent sensible Q H and latent Q E heat fluxes above a suburban reservoir, a micrometeorological turbulence measurement campaign using the eddy covariance technique was carried out between June and November 2012 on the Baldeneysee, an artificial lake (2.64 km 2 area with up to 4-m depth) located in Germany. The study was conducted at this site because there is little information on this type of lake and the findings are important for the local water management system. Sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 41 publications
5
16
0
Order By: Relevance
“…According to the quality control procedure presented above, around 34% of the Hs, 46% of LE and 45% of CO 2 fluxes are removed and the retained data are analyzed in our study. Although the gap ratio is large, it's similar to other studies over 5 lakes (Nordbo et al, 2012;Goldbach and Kuttler, 2015;Shao et al, 2015). A long large gap between August and November of exists in 2014 due to malfunction.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…According to the quality control procedure presented above, around 34% of the Hs, 46% of LE and 45% of CO 2 fluxes are removed and the retained data are analyzed in our study. Although the gap ratio is large, it's similar to other studies over 5 lakes (Nordbo et al, 2012;Goldbach and Kuttler, 2015;Shao et al, 2015). A long large gap between August and November of exists in 2014 due to malfunction.…”
supporting
confidence: 86%
“…LE remains at a higher level during three periods, with an average monthly value of 89.1, 103.9 and 82.2 Wm -2 during pre-monsoon, Monsoon and post-monsoon periods, respectively. The average monthly LE/Rn has a smaller annual variation during pre-monsoon period, which ranges from 0.50 to 0.82 for four-year study 30 period. LE/Rn has a larger fluctuation during monsoon period, which varies from 0.53 to 1 from 2012 to 2015.…”
Section: Monthly Average Energy Balance Components During Different Mmentioning
confidence: 94%
See 1 more Smart Citation
“…The boundary layer method estimates CO 2 flux by the difference in CO 2 concentration between the water and atmosphere and the gas transfer velocity, which is traditionally parameterized only by wind speed (Cole and Caraco, 1998). However, it has been reported that different processes including convection, microwave breaking and stratification could influence the gas transfer velocity (Zappa et al, 2001;Eugster et al, 2003;Podgrajsek et al, 2014). The eddy covariance technique (EC) could provide long-term continuous measurements and the high-resolution data allows for examining the relation between gas exchange velocity and other meteorological variables besides wind speed (Mammarella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The summer monsoon induces an abrupt change in large-scale atmospheric circulation and convective activity over Asia, and carries in air mass with distinct atmospheric properties (i.e., air temperature, wind direction, relative humidity; Li and Yanai, 1996;Lau and Yang, 1997;Zhou et al, 2012). The seasonal reversals of atmospheric properties caused by summer monsoon circulation play an important role in regulating landatmosphere heat and water exchange processes (Flohn, 1957;Hsu et al, 1999). The land-atmosphere exchange processes are found to be closely related to the onset and retreat of summer monsoon (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%